Smart-Care:Sensor Enabled Health Monitoring Sytem - JayaLakshmi, G.; Yalamanchili, Sangeetha (International Journal of Psychosocial Rehabilitation, 2020)
IoT is blustering coupled with artificial intelligence (AI). Leveraging AI with IoT solves various Healthcare issues that the elderly people are facing today. The accurate clinical decisions can be achieved by adopting Data Analytics with help of artificial intelligence algorithms The aged people who cannot move from their homes to hospitals R can be continuously monitors remotely from the hospitals or Health Management systems by means of wearing sensor 50 which measures variance vital signals like respiration rate, heart rate, weight and sleep patterns etc. And the data is sent to a backend system usually a cloud backend for monitoring these patients. Analysis can be done to take necessary medical questions enabling anytime anyway Healthcare reality.